Persepsi Mahasantri Pondok Hajjah Nuriyah Shabran Angkatan 2012 Universitas Muhammadiyah Surakarta Terhadap Hukum Bagi Hasil Bank Syari'ah - Huda, Miftahul, Drs. Harun, MH., Drs.Yayuli, M. PI (2017)
The spirits that became the background for the establishment of Islamic Bank were the willing of Moslems to avoid usury in their muamalah (human relations), the willing to achieve a prosperous life through their muamalah that were suitable with religious orders, and the willing to have another option to implement the banking services in more compatible way. One of the problems that constrains the development of Islamic Bank is the misconception or misunderstanding from society regarding to the operational activities of Islamic Bank. Until right now, the society are still unable to see the differences between syariah bank and conventional bank. The society considers that the Islamic banks and conventional banks are same. Even Islamic banks are seen as banks that only have a relatively higher adminstrative prices. This shows that people do not understand the concept of Islamic banks as Islamic financial institutions. An issue that is appealing to get further investigation is how the perception of the mahasantri (students) of Hajjah Nuriyah Shabran collage of UMS on the law of Islamic bank results. The research objective to be achieved is to know the perception of the mahasantri (students) of Hajjah Nuriyah Shabran collage of UMS on the law of Islamic bank results. This research is a field research, which is carried out directly in the field or real life to know what is happening. The primary data source is the mahasantri (students) of Hajjah Nuriyah Shabran collage of 2012. To achieve these research objectives have been applied methods of data collection such as interviews and documentation. We have analysed the data using qualitative descriptive method. The research has concluded that most mahasantri, 20 of 24 them, understand that the law for the results of Islamic banks is the result done by dividing the profits between the two sides, namely the customer and the bank, which is set at initial contract and there is no usury between the two sides. This is suitable with the Shariah rules and the provisions of Islamic banks and Islamic law.